Supervisi Pembelajaran Sebagai Upaya Mewujudkan Keefektifan Manajemen Kelas - Nunuk Hariyati; Sri Setyowati; Amrozi Khamidi; Vicka Bella Fahira (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to determine the effectiveness of learning supervision in achieving classroom management at the school. The research subjects include a primary school and a kindergarten in Surabaya. The method used in this study is qualitative descriptive with a case study approach. The results indicate a positive correlation between the structured and systematic supervision process, as outlined by Glickman, and the progress in classroom management carried out by teachers. This approach also has a positive impact on student learning outcomes.